1991
DOI: 10.1177/089826439100300104
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Prevalence of Depressive Symptoms in Alameda County

Abstract: Trends in depression are examined using data from the Alameda County Study, a three-wave, prospective community survey covering an 18-year period (1965-1974-1983). Age-period-cohort effects in rates of depressive symptoms were analyzed using logistic regression procedures to adjust for attrition due to loss-to-follow-up and nonresponse. The results indicate the presence of all three effects. There was a marked period effect, with rates in 1974 significantly higher than in either 1965 or 1983. There also was a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 43 publications
3
27
0
1
Order By: Relevance
“…Several authors have hypothesized that the age distribution observed for psychological distress may be confounded by a cohort effect (Brault et al 2011;Chiao et al 2009;Kasen et al 2003;Jorm 2000;Lewinsohn et al 1993;Mirowsky and Kim 2007;Roberts et al 1991;Sacker and Wiggins 2002;Yang 2007). Thus, for instance, young adults might express a higher mean level of distress than older adults not only because they are exposed to more risk factors or because they are more vulnerable to those risk factors, but, at least partly, because they were born at a time when these factors were more prevalent or potentially more harmful.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several authors have hypothesized that the age distribution observed for psychological distress may be confounded by a cohort effect (Brault et al 2011;Chiao et al 2009;Kasen et al 2003;Jorm 2000;Lewinsohn et al 1993;Mirowsky and Kim 2007;Roberts et al 1991;Sacker and Wiggins 2002;Yang 2007). Thus, for instance, young adults might express a higher mean level of distress than older adults not only because they are exposed to more risk factors or because they are more vulnerable to those risk factors, but, at least partly, because they were born at a time when these factors were more prevalent or potentially more harmful.…”
Section: Discussionmentioning
confidence: 99%
“…However, that study did find higher prevalences for those aged 62 years and older (in 1965), 70 years and older (in 1974) and 80 years and older (in 1983). According to Roberts et al (1991), the variation in peak depression prevalence among seniors between 1965 and 1983 could indicate that the age distribution observed in other studies is biased by a cohort effect.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations